Impact of export variety on productivity in Japan - Nguyen, Anh Thu (2016)
This paper underlines the idea of endogenous growth theory that new or higher quality products have significant impacts on productivity and economic growth. Different with previous studies, this paper uses a quite comprehensive definition of variety, which distinguishes the country of origin of the products. With disaggregated level of export data of Japan from 1980 to 2000, the empirical results suggest that nearly half of the industries studied have positive and significant relationship between varieties and Total Factor Productivity (TFP). Most of the industries, which show the positive and significant relationship between export variety and TFP, are secondary industries. This conclusion may bring an implication for Japan to produce more differentiated products to help increase its TFP.